Self-study and inquiry into practice : learning to teach for equity and social justice in the elementary school classroom - Kroll, Linda R. (London ; New York : Routledge, 2012)
"One of the most important factors in making sure that all children achieve well is widely regarded to be a well-prepared teacher and this is particularly the case for those who teach in urban settings. There are new pressures and familiar pressures on teachers and teacher educators to prepare teachers who will be able to teach in a changing world, and who will be able to change the world. The question of how to prepare well-qualified teachers has become an international question with global responses and consequences. This book describes a stance and pedagogy for helping young teachers to be successful in the most challenging of circumstances. Self-Study and Inquiry into Practice: Learning to teach for equity and social justice is about learning to use inquiry to teach in urban settings. The use of inquiry and self-study as ways of thinking about, understanding and developing one's practice and one's teaching can support teachers' continued inspiration and resilience to teach all children well in the face of very challenging circumstances. Using rich examples and case studies of how pre-service teachers and beginning teachers have used inquiry to learn from challenging urban placements, Linda Kroll shows the importance of using inquiry and self-study in learning to teach and in continuing to learn as one teaches. Inquiry and self-study is a useful way to understand what students understand, what they learn from our teaching, and the power and responsibility we have to ensure that all our students achieve their highest potential"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Inquiry-based learning; Research -- Methodology -- Study and teaching (Elementary) -- Case studies; Elementary school teachers -- Training of -- Case studies; Teachers -- Self-rating of -- Case studies; Social justice -- Study and teaching (Elementary); Education, Urban; Critical pedagogy; Electronic books